Antibacterial potential of celery leaf extract toothpaste on the growth of Streptococcus mutans ATCC 25175 - Hayati, Maulida; Mailiza, Fitria; Savitri, Shifa Khumaira (Universitas Padjadjaran, 2023)
ABSTRACTIntroduction: Celery (Apium graveolens L.) is a member of the Apiaceae family that can grow everywhere. Celery contains flavonoids, saponins, tannins, essential oils, apigenin, choline, vitamins A, B, C, asparagine bitter substances. Celery contains flavonoids, saponins, and tannins which are antibacterial compounds. Streptococcus mutans is a Gram-positive bacterium creating an acidic atmosphere in the oral cavity, which causes insufficient saliva to prevent enamel demineralisation which can lead to dental caries. The purpose of this study was to analyze the inhibition effect of celery leaf extract (Apium graveolens L.) on the growth of Streptococcus mutans. Methods: This type of experimental laboratory research uses the Post Test Only Control Group Design. The samples were Apium graveolens L. and Streptococcus mutans ATCC 25175. The number of treatment groups was 24 with concentrations of 20, 40, 60, and 80%. Toothpaste containing antibacterial ingredients was used as positive control and for negative control, a basic toothpaste formula without antibacterial ingredients, namely carboxymethyl cellulose (CMC), xylitol, calcium carbonate (CaCO3), sorbitol, sodium lauryl sulphate (SLS), natrium benzoate. Data analysis using one-way ANOVA test with normality test using Shapiro-Wilk and homogeneity test using Levene test. The results at a concentration of 20, 40, 60 and 80% with a positive control there was no significant difference because the sig value was >0.05. Results: The results showed that Celery containing toothpaste inhibits Streptococcus mutans growth (p value <0.05) that there is a significant inhibition effect of Apium graveolens L. extract toothpaste on the growth of Streptococcus mutans. Conclusion: There is an inhibition effect of celery leaf (Apium graveolens L.) extract toothpaste on the growth of Streptococcus mutans.Keywords: streptococcus mutans ATCC 25175, inhibition, toothpaste, celery, apium graveolens L